Angioinvasive rhinocerebral mucormycosis with complete unilateral thrombosis of internal carotid artery—case report and review of literature - Patil, Aruna (BJR Case Rep, 2016)
Angioinvasive rhinocerebral mucormycosis is an acute fulminant infection caused by fungi of the order Mucorales that targets uncontrolled diabetics and other immunosupressed individuals. Early imaging features of angioinvasiveness include the presence of thrombosed vessels, especially in the orbital regions and the “black turbinate” sign representing devitalized paranasal sinus mucosa. Intracranial extension carries a grave prognosis, with death reported in 90% of cases. This case report highlights the early and key imaging features of angioinvasive rhinocerebral mucormycosis and a rare complication of complete internal carotid artery thrombosis.